The effects of post-harvest dark treatment on the Agar Yield and its quality of Gracilaria changii (xia et Abbott) Abbott, Zhang et Xia - Ting Wei Chin (Terengganu: Universiti Putra Malaysia Terengganu, 2014)
This study is on the effects of post-harvest dark treament (DT) and light treatment(LT) on the agar yield and its qualities (gel strength,GS; melting temperature,MT and gelling temperature,GT) of Gracilaria changii.